Development of Animal Comic Media (Anicom) Oriented with Contextual Approach for Grade X Students - Ilham Sepriadi; Ramadhan Sumarmin; Rahmadhani Fitri (Bioeducation Journal, 2018)
Based on the observation, it was found that the learning process did not motivate the students. Media that teachers use when the learning process is also less interest and motivation of learners. In addition, the media has not provided a clear picture for learners in relating it in everyday life. This study aims to develop a contextually oriented contextual learning medium for a valid and practical X class. This research is a development study. This learning medium was developed using three stages of 4D models. Data obtained from the validation and practicalization. Media that has been designed, validated by three experts, then tested to a teacher and 30 students of class X in SMA Negeri 12 Padang to know the level to the practitioner. The result of the research shows that the media developed in the biology learning oriented contextual approach on the material of kingdom Animalia for students of class X is stated very valid and very practical.